Comparison of hole quality after drilling and helical milling of the Al/CFRP stacks - Doluk, Elżbieta (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2023)
Hybrid sandwich structures composed of aluminium alloys and CFRP (Carbon Fibre Reinforced Polymer) are now frequently used in the aerospace industry. One of the factors inhibiting their application is the difficult processing resulting from the anisotropic nature of this type of construction. These materials are often joined by screws or rivets requiring mounting holes. One of the main problems is ensuring the quality of the holes after machining. The aim of this study is to assess the hole quality (dimensional and shape accuracy) and the occurrence of delamination after machining of a Al 2024/CFRP sandwich structure. In this experiment drilling and helical milling results were compared. A traditional HSS twist drill and a PCD milling cuter with a straight cut were used. The machining was carried out with a variable cutting speed. The tests were performed for two strategy of the machining – Al/CFRP (Al 2024 T3 – Carbon Fibre Reinforced Polymer) and CFRP/Al (Carbon Fibre Reinforced Polymer – Al 2024 T3).